Environmental Tracers - Trevor Elliot (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2014)
Aquifer resources continue to be overexploited, leaving the world's most impoverished (or vulnerable) populations and/or the aquatic environment at an ever increasing risk from climate change. Adaptation strategies demand detailed evaluation and management of water as a resource, requiring an understanding of the chemical, geological (hydrogeological/geohydrological) and biological interactions that waters effect or undergo in the hydrologic cycle. Environmental tracers are ambient natural or man-made compounds widely distributed in the Earth's near-surface. They may be injected into the hydrological system from the atmosphere at recharge and/or are added/lost/exchanged inherently as waters flow over and through materials. Variations in their chemical abundances and isotopic compositions can be used as tracers to determine sources (provenance), pathways (of reaction or interaction) and also timescales (dating) of environmental processes. Water dating may invoke their characteristic decay or accumulation functions, (cf. radioactive and radiogenic compounds and isotopes) in a system or the characteristic injection of sources. Environmental tracers in groundwater systems can give information both on current and past flow conditions independently of hydraulic analyses and modelling. Thus, environmental tracers generically are important tools for developing sustainable management policies for the protection of water resources and the aquatic environment. Recent overviews have highlighted how most environmental tracer systematics have become well-established through proof-of-concept studies in geochemically and hydraulically simple aquifers. The challenge now lies in enhancing the way they are put to use by the hydrologic community and water resource managers in more complex systems (e.g. inter- and intra-aquifer mixing; aquifers as distributed water systems - water coming in at one point is going somewhere, and pumping of water represents an interception) and how they may be used to address issues of vulnerability, sustainability, and uncertainty in water resource systems (including resource, flooding, drought, climate justice, water and food security, water footprints, etc.).